Bibliometric analysis of the Journal of Oral Research. Period 2012-2015. - Ibraín Enrique Corrales; Juan José Reyes; Yasmany Fornaris (Universidad de Concepción., 2016)
Bibliometric studies of scientific publications are useful instruments to evaluate their performance and impact. Objective: To evaluate the scientific production of the Journal of Oral Research in 2012-2015. Materials and Methods: A bibliometric study of the articles and documents published in the period 2012-2015 was performed using descriptive statistics. The variables included in the study were: type and number of articles, classification according to subject and country of origin of the main author. Results: A total of 169 documents were published: 32 editorials, 20 letters to the editor, 69 original articles, 20 case reports, 25 reviews, and 3 study protocols. Countries with the largest number of publications were: Chile with 114, Mexico with 19, Peru 8, and Brazil with 7. Among the 10 most consulted documents in 2015, there were six articles by Chilean authors. Conclusions: During the period 2012-2015 the scientific production of the journal has shown a gradual increase in the number of published documents, with a predominance of original articles written mainly by Chilean and Mexican authors, as well as articles related to primary health care, teaching/bibliometrics and maxillofacial surgery.